Financial Performance Analysis of KSP Berkat Bulukumba In Year 2018-2022 - Nabila, Putri; Omsa, Sirajuddin; Bravely, Irvan (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to determine the health level of KSP Berkat Bulukumba in year 2018-2022 based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises (CSME) of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016. Analysis of the health level of cooperatives is assessed using seven aspects, namely capital aspects, quality of productive assets, management, efficiency, liquidity, independence and growth, as well as aspects of cooperative identity. Data collection in this research was carried out by interviews and questionnaires which were used to measure management aspects and document analysis in the form of balance reports and business revenue residu reports for KSP Berkat Bulukumba for year 2018-2022.The data analysis technique used in this activity is quantitative descriptive. Based on the results of calculating the health level of KSP Berkat Bulukumba for five periods from 2018 to 2022 based on the Regulation of the Deputy for Supervision of the Ministry of CSME of the Republic of Indonesia No.06/Per/Dep.6/IV/2016, it shows a score of 68.65 with predicate 'Pretty Healthy'. During 2018 and 2019 it obtained a score of 68.20, from 2020 to 2022 it increased so that it obtained a score of 68.80.Keywords: Financial performance, KSP Berkat Bulukumba, CSME